A vivência da ação educativa do enfermeiro no programa saúde da família (PSF) - Rodrigo Conti Vieira de Alencar (2006)
This work is a qualitative study aimed at understanding the meaning of the education action attributed to nurses and health community agents by the nurses of the Family Health Program. The method used was the ethnography, based on the theoretical and methodological proposal of SPRADLEY (1979, 1980). The cultural scenario for this work was Cabana, operational and administrative unit, which is part of BeloHorizonte west sanitary district. Data collection was made through participant observation, ethnographic interviews and documentary analysis. The subjects of the research were nine nurses that had been working in the program for over two years.The data analysis identified 8 domains and 6 taxonomies. The results of the research demonstrated some characteristics of the professionals in the Family Health Program, the types of activities developed, and the ways to describe the educational action to the professionals and the community. In relation to the workers, the nurses educational practice is closely related to the traditional and technical conception of education, emphasizing traineeship, professional development and permanenteducation, among other factors. In order to educate, it is necessary to take the worker away from his functions, which implies a disruption in the education conception as a work principle, expression which constitutes the theme of this study.